1995
DOI: 10.1111/1523-1747.ep12317130
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride Blocks a Keratinocyte Nonspecific Cation Channel and Inhibits Ca++ -Induced Keratinocyte Differentiation

Abstract: Proliferation and differentiation in many cells are linked to specific changes in transmembrane ion fluxes. Previously, we have identified a nonspecific cation channel in keratinocytes, which is permeable to and activated by Ca++. To test whether this cation channel might serve as a pathway for Ca++ entry, we examined the effect of blocking this channel on membrane currents, markers of differentiation, and intracellular Ca++. In patch clamp studies, 10(-8) to 10(-6) M amiloride decreased the single-channel ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…The isoforms of adenylyl cyclase expressed by human keratinocytes are presently unknown but fetal rat keratinocytes do express isoforms VI and VIII (Takahashi et al, 1998), meriting further investigation of the adenylyl-cyclase isoforms expressed in human keratinocytes. The mechanism used by keratinocytes to sense and respond to an applied EF does have a very specific requirement for Ca 2+ influx that is not blocked by either amiloride or verapamil (Trollinger et al, 2002) and is, therefore, independent of the non-specific cation channel (Mauro et al, 1995) previously identified.…”
Section: Discussionmentioning
confidence: 91%
“…The isoforms of adenylyl cyclase expressed by human keratinocytes are presently unknown but fetal rat keratinocytes do express isoforms VI and VIII (Takahashi et al, 1998), meriting further investigation of the adenylyl-cyclase isoforms expressed in human keratinocytes. The mechanism used by keratinocytes to sense and respond to an applied EF does have a very specific requirement for Ca 2+ influx that is not blocked by either amiloride or verapamil (Trollinger et al, 2002) and is, therefore, independent of the non-specific cation channel (Mauro et al, 1995) previously identified.…”
Section: Discussionmentioning
confidence: 91%
“…Although intracellular pH has been linked to diverse cellular functions in various tissues, including cell proliferation, trans- formation, and differentiation (1,33,34), extracellular acidification also occurs in a regulated manner. The NHE family of Na ϩ /H ϩ exchangers is ubiquitous, and their role in acid-base balance is best understood in kidney (33), where concentrationdriven influx of Na ϩ provides the driving force for the NHEmediated extrusion of H ϩ into the extracellular domain.…”
Section: Nhe1 Regulates Epidermal Ph and Barrier Functionmentioning
confidence: 99%
“…Cultured keratinocytes express the sodium-proton exchanger (NHE) 1 class of non-energy-dependent transporters, which controls intracellular pH (1). Recently, the NHE1 isoform has been shown to be the only isoform in keratinocytes and epidermis (2).…”
mentioning
confidence: 99%
“…Transglutaminase activities require Ca 2ϩ as cofactor (36,37,40). Amiloride blocks cell Ca 2ϩ influx, and by this mechanism it has been reported to inhibit Ca 2ϩ -induced keratinocyte differentiation and CE formation (41). Cystamine is a water-soluble primary amine that inhibits transglutaminase activities by competing with ⑀-lysines in endogenous protein substrates (42,43).…”
Section: The Cyp2b19 Metabolite 1415-eet Activates Keratinocytementioning
confidence: 99%